Analysis of 3D printing filament using Polyvinyl Alcohol (PVA) / M. I. S. Suliman ... [et al.] - Suliman, M. I. S.; Rizal, N. A. M.; Azmee, M. N. I.; Abdullah, A. H.; Makhtar, A. K.; Adull Manan, N. F. (Smart Manufacturing Research Institute (SMRI), 2024)
The widespread adoption of 3D printing as a manufacturing method across various industries offers a diverse range of filaments tailored to specific printing requirements. However, the production of intricate designs presents challenges, particularly in the removal of support structures. This research explores the manual removal and aqueous dissolution times, evaluating resultant model quality. Categorizing eighteen samples into simple, medium and complex groups, with each comprising three units, forms the basis for assessing Polyvinyl Alcohol (PVA) filament’s impact on support structures and overall model quality. Nine samples exclusively used Polylactic Acid (PLA) as a control group, while the remaining nine integrated PVA filament, ensuring a comprehensive examination of PVA's influence on different design complexities. For meticulous design, Autodesk TinkerCAD meticulously guides the design process with precision, utilizing two 3D printers of Creality Ender 3 that exclusively uses PLA filament, and the Ultimaker 3 Extended which is equipped with dual print cores that utilize both PLA and PVA filaments. The inclusion of PVA as a support material proves pivotal in facilitating the printing of intricate designs due to its facile removal and environmentally friendly properties. The PVA is better at support compared to PLA with lesser damage. This study significantly contributes to optimizing 3D printing processes, addressing challenges related to intricate designs and support structure removal. The findings are relevant for industries relying on precise components through 3D printing, marking a stride towards enhanced manufacturing efficiency.